METHODOLOGICAL APPROACH TO THE IMPLEMENTATION OF INTEGRATED MANAGEMENT SYSTEMS FOR SMALL AND MEDIUM-SIZED ENTERPRISES - Sandra Cecilia Baustista Rodriguez U; Guillermo Peña Guarín; Amable José Pérez (International Journal for Quality Research, 2024)
Today's business environment infers organizational competitiveness that encourages organizations to adopt standardized systems that facilitate effective business management. Small and medium-sized enterprises (SMEs) promote economic growth and equitable development; however, few works offer approaches that include the dynamics and resource constraints of SMEs. Hence, this paper proposes a method for integrating management systems in SMEs that articulates the continuous management cycle of Plan, Do, Check, Act (PDCA), with a four-phase implementation sequence: (1) Direction, (2) Structuration, (3) Application, (4) Evaluation and Improvement. It also discusses how SMEs can integrate their management systems with the knowledge necessary to reduce or mitigate risks arising from the organization's interactions with its stakeholders. This research advances the proposal of a practical sequence for building and implementing the integrated management system and presents the key strategic, operational and human factors as an innovative element to facilitate the understanding, implementation, evaluation and improvement of the IMS in SMEs.